2021
DOI: 10.1109/jiot.2021.3069878
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cost-Effective Controller Placement Scheme for Software-Defined Vehicular Networks

Abstract: Energy costs have dramatically increased in data center networks as an increasing number of large-scale Internet applications are used. In software-defined vehicular networks (SDVN), the communication delay between two vehicles and between vehicles and the controller will dramatically climb up as the number of vehicles increases. This requires more controllers to provide communication service to minimize the latency. More controllers lead to high energy costs. Therefore, the number of controllers and their pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…From their simulation results, Lin et al 116 concluded that the proposed robust controller placement heuristic algorithm with an integer linear programming (RCP‐ILP) enhances the robustness, the efficiency and load balancing of SDNs at the cost of least controllers placement against links failure.…”
Section: Performance Metrics In Sdnmentioning
confidence: 99%
“…From their simulation results, Lin et al 116 concluded that the proposed robust controller placement heuristic algorithm with an integer linear programming (RCP‐ILP) enhances the robustness, the efficiency and load balancing of SDNs at the cost of least controllers placement against links failure.…”
Section: Performance Metrics In Sdnmentioning
confidence: 99%
“…In addition, they considered reducing latency in their work. Lin et al [23] proposed a new controller placement scheme to reduce costs for software-defined vehicular networks. In the proposed method, first, the minimum number of controllers is selected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…E itself contains the links connecting the controller to the switch and the controller to the controller indicated by the symbols E F and E S , respectively. Links are considered directional when the process of controller placement and Methods Objectives Latency Scalability Reliability Cost [7] The average latency and worst-case latency * --- [10] Integer linear programming * --* [11] Integer linear programming * -* - [12] The spectral clustering algorithm -* * - [13] Determining the failure rate --* - [14] Graph parsing algorithm * -* - [15] The spanning tree topology * --* [16] Using an efficient algorithm * --- [17] Cluster of multiple controllers * * * - [18] Tree subgraph * -* - [19] Hierarchical clustering * * * - [20] Integer linear programming * * -* [21] Using the clique algorithm * * * - [22] Varna optimization method * * * - [23] Bee colony algorithm * * -* [24] RetroFlow algorithm * -* - [25] Programmability guardian * * * - [26] Integer linear programming * -* - [27] Matchmaker assigning switches to them is called. In this way, the switches are connected to their controllers and the controllers are connected to each other.…”
Section: The Mathematical Expression Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…These single SDN controllers are mostly suitable for small coverage networks (i.e., local area networks) [6]. Some of the prior works exploit single SDN controllers for small coverage networks; however, they face single-point failure and scalability issues [7]. The use of a…”
Section: Introductionmentioning
confidence: 99%